Personal Emergency Alert Device Containing Real-Time Location - Liwanag, Stephanie E.; Alfaro, Ma. Andrea A.; Carlos, Wilfred I.; Cruz, Jerald B.; Guevarra, Rea G.; Layco, Eddiebal P.; Villanueva, Louie Fe S. (International Journal of Computing Sciences Research; Vol 6 (2022): Vol 6, 2022)
Purpose – The purpose of this study is to develop a Personal Emergency Alert Device Containing Real-time Location which can be used by anyone particularly women and children who need help especially in times of emergency. Method – Arduino Nano, Global Positioning System, and Global System for Mobile Communication were utilized as the main components of the device, which was evaluated in the aspect of appearance through its size, weight, product design, casing, and functionality through its accuracy in displaying information, text messaging capabilities, and location tracking. In order to optimize the product’s specifications, it underwent assessment and evaluation by experts in the field. The study used product development design. There were twenty (20) respondents in total, comprising of five (5) Electronics Engineer and fifteen (15) Electronics Engineering students who were selected using purposive sampling techniques. The responses were gathered from the students by handing out questionnaires, which were eventually tallied, tabulated, processed and treated using statistical treatment. Results – The structure of the device is excellent. The product also passed the evaluation of the expert respondents in terms of functionality since it is excellent in accessing the information, delivering the right information, and finding exact locations. The device is thus functional as it serves its purpose. Conclusion – The structure of the device is excellent. The product also passed the evaluation of the expert respondents in terms of functionality since it is excellent in accessing the information, delivering the right information, and finding exact locations. The device is thus functional as it serves its purpose. Recommendations – It is recommended that the product developers should reduce the device size. They should also ensure that the casing and design are attractive to make the device noticeable. Moreover, to further improve the functionality of the device, product developers should track the exact location instead of coordinates. They should also consider which cellular network works best for different places. Lastly, to augment the results and findings of this study, further research undertakings on this topic should be conducted. Research Implications – The users of this product can help summon assistance in case of emergency. Practical Implications – Anyone who is experiencing emergency cases will just press the button for them to be tracked and be saved.